Quality, Non-clinical and Clinical Considerations for Biosimilar Monoclonal Antibody Development: EU, WHO, USA, Canada, and BRICS-TM Regulatory Guidelines - Rahalkar, Hasumati; Cetintas, Hacer Coskun; Salek, Sam (Frontiers in Pharmacology, 2018)
Objectives: The aim was to critically evaluate well-established regulatory agencies mAb biosimilar guidelines for development and marketing authorization about quality, efficacy and safety and compare to BRICS-TM regulations to identify challenges. Materials and Methods: The current valid guidelines of EMA, WHO, USFDA, HC/BGTD, ICH and BRICS-TM were obtained from official websites and comparative qualitative review was performed. Results: The review revealed that Health Canada uses mAb specific guidelines from EMA or USFDA when necessary. The BRICS agencies (except Russia) have incorporated some or most of the WHO SBP TRS and related annexes in similar national biotechnological/biological guidelines; however, gaps or insufficient information have been identified. The Russian Federation has issued general product registration guideline/s with very brief information about mAbs. The TMMDA (Turkey) has published an updated biosimilar guideline which parallels those of the EMA and the ones from WHO; however, no mAb specific guidelines are published. COFEPRIS (Mexico) has published a biotechnological/biological product registration guideline with no information about mAb. The SAHPRA biosimilar guideline has an annex on mAbs which focuses on non-clinical and clinical aspects. The comparative evaluation of BRICS-TM agencies indicates a gap pertaining to clarification for physico-chemical characterization, manufacturing process, overages and compatibility requirements between biological substances and excipients specifically on mAbs. In vitro assay requirements seem quite aligned with those of WHO, whereas in vivo studies mostly have disparity in terms of necessity, type of studies as well as design and criteria. Clinical safety and efficacy studies are indicated in emerging regulatory agencies, however detailed information pertaining to design, size of populations, requirements for primary and secondary endpoints, clarity and evaluation criteria differ. In general, BRICS-TM agencies allow extrapolation of indications provided that pre-defined conditions are met. Interchangeability, switching and substitution of biosimilars are not defined in most of BRIC-TM guidelines whereas South Africa, by law, allows neither interchangeability nor substitution. Pediatric research remains questionable across BRICS-TM. Conclusions: EMA, USFDA guidelines are broadly aligned with WHO and in addition, they also contain specific requirements pertaining to their own region. BRICS-TM has considerably less defined mAb specific biosimilar development and comparability parameters in their published guidelines.